Removing barriers for sustainability: A qualitative cross-country analysis of entrepreneurial ecosystem attributes in Israel and Germany - Louisa Jantos; Philipp Bäumle; Daniel Feser (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2024)
There is a growing scholarly and political consensus about the potential of entrepreneurial ecosystems (EEs) to further sustainability by fostering sustainable start-ups. However, little is known about how the constituents of EEs as institutional framework for entrepreneurship affect the success of sustainable start-ups. Based on institutional theory, this paper develops and tests a conceptual framework to assess how the configuration of EE components affect mature EEs in their ability to support sustainable start-ups. Based on semi-structured interviews with EE stakeholders from Tel Aviv and Berlin, along with site visits and participatory observations, this cross-country analysis demonstrates that the attributes represent a promising explanatory approach for the sustainability alignment of an EE. The empirical results are threefold: (1) sustainable start-ups have special needs regarding their institutional environment and (2) require a more distinctive support structure surpassing the level of an EE. Hence, (3) each institutional component has to be tackled according to its spatial relevance to further sustainability. This translates into differentiated policy implications for fostering sustainability and theoretical advancements in EE research regarding spatial integration of sustainable start-up support. We contribute to institutional and entrepreneurship literature by implementing the idiosyncrasies of an EE's ability to further sustainability through their attributes. – – Ein wachsender wissenschaftlicher und politischer Konsens besteht darüber, dass unternehmerische Ökosysteme (EEs) durch die Förderung nachhaltiger Unternehmensgründungen zur Nachhaltigkeit beitragen können. Jedoch ist nur wenig darüber bekannt, wie die Bestandteile von Ökosystemen als institutioneller Rahmen für Unternehmertum den Erfolg nachhaltiger Unternehmensgründungen beeinflussen. Auf der Grundlage der Institutionstheorie wird in diesem Beitrag ein konzeptioneller Rahmen entwickelt und getestet, um zu beurteilen, wie die Konfiguration der EE-Komponenten reife EEs in ihrer Fähigkeit, nachhaltige Unternehmensgründungen zu unterstützen, beeinflusst. Auf der Grundlage von semi-strukturierten Interviews mit EE-Akteur*innen aus Tel Aviv und Berlin sowie Standortbesuchen und teilnehmenden Beobachtungen zeigt diese länderübergreifende Analyse, dass die Attribute einen vielversprechenden Erklärungsansatz für die nachhaltige Ausrichtung eines EEs darstellen. Die empirischen Ergebnisse zeigen folgendes: (1) Nachhaltige Gründungen haben besondere Anforderungen an ihr institutionelles Umfeld und (2) benötigen eine ausgeprägtere Unterstützungsstruktur, die über das Niveau eines EEs hinausgeht. Folglich muss (3) jede institutionelle Komponente entsprechend ihrer räumlichen Relevanz für die Ausrichtung auf Nachhaltigkeit angegangen werden. Daraus ergeben sich differenzierte politische Implikationen für die Nachhaltigkeitsförderung und theoretische Weiterentwicklungen innerhalb der EE-Forschung in Bezug auf die räumliche Integration nachhaltiger Gründungsförderung. Indem die Besonderheiten der Fähigkeit eines EEs zur Förderung der Nachhaltigkeit durch ihre Eigenschaften umgesetzt werden, wird hiermit ein Beitrag zur Institutions- & Unternehmertumsliteratur geleistet.
Keywords: O31; O38; Q01; R11; 330; entrepreneurial ecosystem; sustainable start-ups; case study; institutional theory